Analisis Termodinamika dan Kinetika Nanopartikel Karbon (C-Dot) dari Buah Durian Sebagai Inhibitor Korosi Tembaga: Thermodynamics and Kinetics Analysis of Carbon-Dots from Durian as Copper Corrosion Inhibitor - Faradisa Anindita; Noviyan Darmawan; Zainal Alim Mas'ud (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2021)
Corrosion is a physical interaction between the metal and its environment, which results in changes in the metal's properties due to chemical or electrochemical reactions. The corrosion rate can be reduced by adding a corrosion inhibitor. Uses of nanotechnology for corrosion prevention is one of the first technical because almost made structures rely on the stability of a 1–2 nm thick passive film which provides stability to the underlying material. Herein we report the thermodynamic and kinetic analysis of carbon-dots from Durian as inhibitor copper corrosion. To test the anticorrosive performance and analyze thermodynamic properties in its role as a corrosion inhibitor on copper using potentiodynamic polarization. The thermodynamic-kinetic parameters of corrosion obtained values of H‡ = 60.44 kJmol-1, ΔS‡ = -73.9 kJmol-1, and ΔG‡ = 82.83 kJmol-1, show that the attendance of C-dot as a corrosion inhibitor causes a non-spontaneous reaction rate to be proven by increasing spontaneity (ΔG‡). The value of activation energy samples was higher than the blank, indicates the presence of C-dot effective to reduce the rate of corrosion of the metal.